2020
DOI: 10.3390/ijerph17186755
|View full text |Cite
|
Sign up to set email alerts
|

A Reversal of the Association between Education Level and Obesity Risk during Ageing: A Gender-Specific Longitudinal Study in South Korea

Abstract: This study aimed to examine and quantify obesity risk across different education levels during ageing using the dataset of a nationally representative longitudinal survey. A total of 45,391 observations of 9991 individuals aged ≥45 years were included in this study. Obesity was defined as a body mass index of ≥25, according to a guideline for Asians by the World Health Organization, and education level was grouped into three categories. Socio-demographics, lifestyles, and health conditions were used as covaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…In total, 85 studies reported on associations between education and obesity defined using BMI ( Table S3 ). There were eight longitudinal studies (follow-ups were five ( Camões et al, 2010 ), 10 ( Chung and Kim, 2020 ), 13 (von Hippel & Lynch, 2014) , 14 ( Coogan et al, 2012 ), 23 ( Salsberry and Reagan, 2009 ), 29 (Cohen, Rehkopf, Deardorff, & Abrams, 2013b) , 33 ( Salonen et al, 2009 ) and 36 years ( Kim, 2016 )). Six studies reported results of multiple countries ( Devaux & Sassi, 2013 ; Drewnowski et al, 2005 ; Hughes et al, 2017 ; Klumbiene et al, 2004 ; Roskam et al, 2010 ; Sarlio-Lähteenkorva et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 85 studies reported on associations between education and obesity defined using BMI ( Table S3 ). There were eight longitudinal studies (follow-ups were five ( Camões et al, 2010 ), 10 ( Chung and Kim, 2020 ), 13 (von Hippel & Lynch, 2014) , 14 ( Coogan et al, 2012 ), 23 ( Salsberry and Reagan, 2009 ), 29 (Cohen, Rehkopf, Deardorff, & Abrams, 2013b) , 33 ( Salonen et al, 2009 ) and 36 years ( Kim, 2016 )). Six studies reported results of multiple countries ( Devaux & Sassi, 2013 ; Drewnowski et al, 2005 ; Hughes et al, 2017 ; Klumbiene et al, 2004 ; Roskam et al, 2010 ; Sarlio-Lähteenkorva et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of this study, the relationship between education and the BMI of people with disabilities was not significant. Previous studies [ 12 , 40 , 41 ] reported that the BMI values of people with lower education fell within the higher range compared to people with higher education. However, studies on the mechanism of the effect of education level and the BMI of people with disabilities could not be confirmed.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have explored the relationship between SES (education and income in this study) and obesity, and evidence has shown that SES was strongly related to obesity in prospective cohort studies (29‐32). The framework of social determinants of health suggests that material, psychosocial, and behavioral factors contribute to the explanation of SES inequalities in obesity (33).…”
Section: Discussionmentioning
confidence: 99%